2021
DOI: 10.1021/acsomega.1c01919
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Propped Fracture Conductivity Correlations of Several Shale Formations

Abstract: In hydraulic fracturing operations, small rounded particles called proppants are mixed and injected with fracture fluids into the targeted formation. The proppant particles hold the fracture open against formation closure stresses, providing a conduit for the reservoir fluid flow. The fracture’s capacity to transport fluids is called fracture conductivity and is the product of proppant permeability and fracture width. Prediction of the propped fracture conductivity is essential for fracture design optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…These ML techniques are mostly used for various tasks, such as classification, regression, and data analysis . Each algorithm has its unique characteristics and advantages, which make it suitable for different types of problems. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ML techniques are mostly used for various tasks, such as classification, regression, and data analysis . Each algorithm has its unique characteristics and advantages, which make it suitable for different types of problems. …”
Section: Methodsmentioning
confidence: 99%
“… 34 Each algorithm has its unique characteristics and advantages, which make it suitable for different types of problems. 35 37 …”
Section: Methodsmentioning
confidence: 99%
“…ML and artificial intelligence techniques have widely been implemented in the oil and gas industry for various applications such as reservoir characterization, well logging interpretations, reservoir engineering applications, production engineering, chemical analysis, and so forth. …”
Section: Methodsmentioning
confidence: 99%
“…It showed that the FLS is a powerful predictive tool for well stimulation, reservoir geomechanics, and permeability evaluation aspects. Furthermore, AI models, especially the ANN, assisted in foreseeing the capacity of propped hydraulic fractures to conduit fluids in gas shale zones. , In line with that, Artun utilized the ANN to recognize the connectivity between injector and producer wells using neural network weights into the features. In addition, the capability of ML methods in reservoir simulation was assessed by Ghassemzadeh et al through incorporating an extensive range of reservoir data and creating a deep net simulator (DNS).…”
Section: Introductionmentioning
confidence: 97%